Simple route to lithium dendrite prevention for long cycle-life lithium metal batteries. (June 2021) - Ghosh, Arnab; Cherepanov, Pavel; Nguyen, Cuong; Ghosh, Arpita; Kumar, Ajit; Ahuja, Aakash; Kar, Mega; MacFarlane, Douglas R.; Mitra, Sagar
Abstract: We report an effective approach to control the growth of Li3 N nanosheets on lithium anode. Comprehensive density functional theory (DFT)-based theoretical studies unveil the favorable growth directions of the Li3 N nanosheets on Li metal substrate. The homogeneous layer of vertically grown Li3 N nanosheets helps lithium-sulfur batteries to achieve exceptional dynamic as well as static stabilities. At high current rate of 2C (1C = 1672 mA h g –1 ), a lithium-sulfur battery containing the Li3 N-passivated Li anode exhibits stable cycling performance over 1000 cycles, with average Coulombic efficiency of ~ 99.6%. A fully charged lithium-sulfur battery exhibits a highly stable open circuit potential (OCP) over 30 days of resting. Current outcomes open up an encouraging route to stabilize the lithium anode interface for the high-energy rechargeable lithium metal batteries. Graphical abstract: Image, graphical abstract